Xenophagy receptors Optn and p62 and autophagy modulator Dram1 independently promote the zebrafish host defense against Mycobacterium marinum - Xie, Jiajun; Meijer, Annemarie H. (Frontiers in Cellular and Infection Microbiology, 2024)
Anti-bacterial autophagy, also known as xenophagy, is a crucial innate immune process that helps maintain cellular homeostasis by targeting invading microbes. This defense pathway is widely studied in the context of infections with mycobacteria, the causative agents of human tuberculosis and tuberculosis-like disease in animal models. Our previous work in a zebrafish tuberculosis model showed that host defense against Mycobacterium marinum (Mm) is impaired by deficiencies in xenophagy receptors, optineurin (Optn) or sequestome 1 (p62), and Damage-regulated autophagy modulator 1 (Dram1). However, the interdependency of these receptors and their interaction with Dram1 remained unknown. In the present study, we used single and double knockout zebrafish lines in combination with overexpression experiments. We show that Optn and p62 can compensate for the loss of each other's function, as their overexpression restores the infection susceptibility of the mutant phenotypes. Similarly, Dram1 can compensate for deficiencies in Optn and p62, and, vice versa, Optn and p62 compensate for the loss of Dram1, indicating that these xenophagy receptors and Dram1 do not rely on each other for host defense against Mm. In agreement, Dram1 overexpression in optn/p62 double mutants restored the interaction of autophagosome marker Lc3 with Mm. Finally, optn/p62 double mutants displayed more severe infection susceptibility than the single mutants. Taken together, these results suggest that Optn and p62 do not function downstream of each other in the antimycobacterial xenophagy pathway, and that the Dram1-mediated defense against Mm infection does not rely on specific xenophagy receptors.